Alendronate crosslinked chitosan/polycaprolactone scaffold for bone defects repairing - Shi, W.; Zhang, X.; Bian, L.; Dai, Y.; Wang, Z.; Zhou, Y.; Lu, X.
Here, we evaluated osteogenic differentiation in vitro and new bone formation in vivo using an alendronate-loaded chitosan/polycaprolactone scaffold (CS/PCL)in rats with a critical-sized calvarial defect. Through the action of genipin, which has a crosslinking function, alendronate (AL)was anchored throughout the CS/PCL composite scaffold (CS/PCL@AL)to form an AL sustained release system. We demonstrated that CS/PCL@AL scaffolds significantly enhanced the osteogenic differentiation of ectomesenchymal stem cells (EMSCs)in vitro. Additionally, we explored the possible molecular mechanism of CS/PCL@AL scaffolds in the osteogenic differentiation of EMSCs. This composite scaffold exerted two positive effects on EMSC osteogenic differentiation: 1)the CS/PCL@AL scaffold enhanced EMSC osteogenic differentiation by upregulating bone morphogenetic protein 2, interleukin 10 and laminin expression; and 2)the CS/PCL@AL scaffold promoted the osteogenic differentiation of EMSCs by activating the yes-associated protein (YAP)signaling pathway. YAP and its downstream target transglutaminase are crucial mediators in the osteogenic differentiation of EMSCs. Finally, micro-computed tomography analyses and histology results suggested that the CS/PCL@AL scaffold exhibited a superior capacity to accelerate new and mature bone formation in skull bone defects in Sprague-Dawley rats. This simple and low-cost technology may represent a promising strategy to construct an efficient delivery system to repair bone defects.
Keywords: CHITOSAN; ALENDRONATE; PCL